Marcus Tullius Cicero: Levelek – Kr. e. 45–44, Havas László, Óbis Hajnalka (ford.), Budapest, Károli Gáspár Református Egyetem – L’Harmattan, 2021, 244 pp. - Frazer-Imregh, Monika (Antikvitás & Reneszánsz, 2022)
Marcus Tullius Cicero: Levelek – Kr. e. 45–44, Havas László, Óbis Hajnalka (ford.), Budapest, Károli Gáspár Református Egyetem – L’Harmattan, 2021, 244 pp.